A protein activator of Mg(2+)-dependent, Ca(2+)-stimulated ATPase in human erythrocyte membranes distinct from calmodulin - Mauldin, Douglas (1980)
Treatment of extensively washed erythrocyte membranes with 0.1mm-EDTA decreased their Mg(2+)-dependent, Ca(2+)-stimulated ATPase [(Mg(2+)+Ca(2+))-ATPase] activity. An activator released by this treatment restored the (Mg(2+)+Ca(2+))-ATPase to its original value in a Ca(2+)-dependent manner. This activator was different from calmodulin, as determined by a number of criteria. It was retained on an Amicon XM-100 ultrafiltration membrane (molecular-weight cut-off 100000); it appeared in the void volume of Sephadex G-100 and G-75 columns; it was not retained on a DEAE-cellulose ion-exchange column at ionic strengths similar to those used to retain calmodulin; and it maximally activated (Mg(2+)+Ca(2+))-ATPase activity less than calmodulin and at a higher Ca(2+) concentration. Like calmodulin, the activator is heat-stable. The activator fraction isolated on a 2.5–15% sucrose gradient in 0.16m-KCl showed a single band of mol.wt. 63000 and no calmodulin on 10%-polyacrylamide/sodium dodecyl sulphate gels. A trace amount of calmodulin was detected in the activator fraction by radioimmunoassay (approx. 10pg/ml of `ghosts'), but this amount was insufficient to account for the (Mg(2+)+Ca(2+))-ATPase activation. Furthermore, calmodulin-binding protein failed to inhibit (Mg(2+)+Ca(2+))-ATPase activity by more than 10–20% in the membrane preparations from which the activator was extracted. It was concluded that erythrocyte membranes contain a (Mg(2+)+Ca(2+))-ATPase activator that may attenuate the activation of the Ca(2+)-transport ATPase by calmodulin.